2017
DOI: 10.1176/appi.neuropsych.16090168
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Presentations of C9orf72 Mutation: What Are the Diagnostic Implications for Clinicians?

Abstract: The C9orf72 mutation was identified as the most frequent genetic cause of frontotemporal dementia (FTD). In light of multiple reports of predominant psychiatric presentations of FTD secondary to C9orf72 mutation, the American Neuropsychiatric Association Committee on Research reviewed all studies on psychiatric aspects of this mutation to identify clinically relevant features for diagnosis. The most common psychiatric presentation is psychosis (21%-56%), with delusions, and/or multimodal hallucinations. Other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 95 publications
(172 reference statements)
7
57
0
1
Order By: Relevance
“…Atrophy in this nucleus can lead to altered processing of pain, hallucinations, and both affective and psychotic symptoms. This is in line with frequently reported clinical symptoms in C9orf72 carriers that tend not to be found in other forms of FTD (Ducharme, Bajestan, Dickerson, & Voon, 2017;Fletcher et al, 2015). We also found that the LGN was particularly affected in C9orf72, an area previously linked to visual hallucinations which are a common feature of this genetic group (Ducharme et al, 2017;Kertesz et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Atrophy in this nucleus can lead to altered processing of pain, hallucinations, and both affective and psychotic symptoms. This is in line with frequently reported clinical symptoms in C9orf72 carriers that tend not to be found in other forms of FTD (Ducharme, Bajestan, Dickerson, & Voon, 2017;Fletcher et al, 2015). We also found that the LGN was particularly affected in C9orf72, an area previously linked to visual hallucinations which are a common feature of this genetic group (Ducharme et al, 2017;Kertesz et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…The pulvinar is a key region for limbic functions and intramodality integration of sensory information (Schmahmann, 2003) ( Table 1). This is in line with frequently reported clinical symptoms in C9orf72 carriers that tend not to be found in other forms of FTD (Ducharme, Bajestan, Dickerson, & Voon, 2017;Fletcher et al, 2015). This is in line with frequently reported clinical symptoms in C9orf72 carriers that tend not to be found in other forms of FTD (Ducharme, Bajestan, Dickerson, & Voon, 2017;Fletcher et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…because the hexanucleotide repeat is reported to have a frequency less than 0.1% in those with schizophrenia. 32 We found increased rates of recorded cardiovascular disease (CVD) before diagnosis of ALS (RR = 1.21; 95% CI, 1.15-1.27), as previously reported. 16 This association, however, was not detected in the narrow definition of heart disease; MI.…”
Section: Discussionsupporting
confidence: 84%
“…An increased prevalence of psychotic symptoms in FTD patients with C9orf72 expansion has been reported. However, a recent comprehensive review concluded that the prevalence of C9orf in primary psychiatric presentations is estimated to be around 0.1% 15 and not larger than its prevalence in healthy controls. A possible association with Alzheimer's disease (AD) has also been examined.…”
Section: Background Discovery and Clinical Significance Of C9orf72mentioning
confidence: 99%